Interactions of metals and Apolipoprotein E in Alzheimer’s disease - Xu, He; Finkelstein, David I.; Adlard, Paul A. (Frontiers in Aging Neuroscience, 2014)
Alzheimer’s disease (AD) is the most common form of dementia, which is characterized by the neuropathological accumulation of extracellular amyloid plaques and intracellular neurofibrillary tangles (NFTs). Clinically, patients will endure a gradual erosion of memory and other higher order cognitive functions. Whilst the underlying etiology of the disease remains to be definitively identified, a body of work has developed over the last two decades demonstrating that AD plasma/serum and brain are characterized by a dyshomeostasis in a number of metal ions. Furthermore, these metals (such as zinc, copper and iron) play roles in the regulation of the levels AD-related proteins, including the amyloid precursor protein (APP) and tau. It is becoming apparent that metals also interact with other proteins, including apolipoprotein E (ApoE). The Apolipoprotein E gene (APOE) is critically associated with AD, with APOE4 representing the strongest genetic risk factor for the development of late-onset AD whereas APOE2 appears to have a protective role. In this review we will summarize the evidence supporting a role for metals in the function of Apolipoprotein E (ApoE) and its consequent role in the pathogenesis of AD.